Evidence for a limit to human lifespan - Dong, Xiao; Milholland, Brandon; Vijg, Jan (Nature (London), 2016)
Demographic analysis of life expectancy and maximum reported age at death provides evidence that human lifespan has reached its natural limit. Natural constraints on human lifespan We often hear that we are living longer. In fact, many of the historical gains in life expectancy are attributable to reductions in early-life mortality, although there is recent evidence for some decline in late-life mortality. In this paper, Jan Vijg and colleagues address the vexed question of whether there is a fundamental limit to human longevity. Their demographic analysis of life expectancy and maximum reported age at death supports the idea that human lifespan has a 'natural limit'. Improvements in survival with age tend to decline after age 100, and the age at death of the world's oldest person has not increased since the 1990s. Driven by technological progress, human life expectancy has increased greatly since the nineteenth century. Demographic evidence has revealed an ongoing reduction in old-age mortality and a rise of the maximum age at death, which may gradually extend human longevity 1 , 2 . Together with observations that lifespan in various animal species is flexible and can be increased by genetic or pharmaceutical intervention, these results have led to suggestions that longevity may not be subject to strict, species-specific genetic constraints. Here, by analysing global demographic data, we show that improvements in survival with age tend to decline after age 100, and that the age at death of the world’s oldest person has not increased since the 1990s. Our results strongly suggest that the maximum lifespan of humans is fixed and subject to natural constraints.